Caracterização físico-química e reológica de triticale (x Triticosecale wittmack) visando à aplicação em biscoito tipo cookie - Watanabe, Érika (2016)
Triticale is a hybrid cereal resulting from artificial crossing between wheat and rye. Being resistant to environmental stresses and presenting good nutritional attributes, it has the potential to increase the world food supply, providing an alternative grain to wheat. This research investigated the physicochemical and rheological properties of triticale with the purpose of applying its flour in cookies. The grains of thirteen genotypes of triticale and two wheat varieties, used for comparative purposes, were analyzed for the occurrence of germination, hectoliter weight, moisture, protein, lipids, ash, starch, falling number and volume of sedimentation in SDS. Afterwards, they were conditioned to 15,5% of moisture, submitted to grinding and evaluated for total flour extraction rate and percentage of breakage and reducing fractions. Flours were analyzed for moisture, ash, color, gluten, solvent retention capacity and farinography. The triticales differentiated of wheats by lower protein content (except BRS Ulisses), higher amount of ash and lower performance in the tests of falling number, sedimentation volume and farinograph parameters such as development time and stability of mass. Moreover, they had lower gluten content, including varieties that it was not possible to detect by conventional method. According to the characteristics, triticales do not show suitability for panification, but could be used in malting to produce fermented beverages, as additives of flour with high falling number, extruded foods, cereal bars, breakfast cereals, multigrain mix and formulations that do not require flour with high gluten strength, such as cookies and cakes. Two triticales: TLD 1202 and BRS Minotauro, with different gluten levels were selected to replace the wheat flour LD 122105 in the production of cookies. Three cookies formulations were prepared, each containing only one of the flours. The cookies were subjected to proximate composition, mass measurement (before and after baking), diameter, thickness, cookie factor, and instrumental color and texture analysis. The microbiological safety of cookies was guaranteed through the tests required by current legislation and subsequent application of the acceptance tests. The cookies produced with triticale had lower protein content, but larger diameter and consequently, greater expansion factor. The replacement of wheat flour by triticale also reduced hardness and friability of cookies and in sensory terms, although the three formulations had been well accepted, those prepared with triticale flour achieved the best scores. Thus it was possible to completely replace wheat flour by triticale in the cookie formulation, keeping the product characteristics and regardless of the amount of gluten of flour.